Widespread dissemination of class 1 integron components in soils and related ecosystems as revealed by cultivation-independent analysis - Jechalke, Sven; Schreiter, Susanne; Wolters, Birgit; Dealtry, Simone; Heuer, Holger; Smalla, Kornelia (Frontiers in Microbiology, 2014)
Class 1 integrons contribute to the emerging problem of antibiotic resistance in human medicine by acquisition, exchange, and expression of resistance genes embedded within gene cassettes. Besides the clinical setting they were recently reported from environmental habitats and often located on plasmids and transposons, facilitating their transfer and spread within bacterial communities. In this study we aimed to provide insights into the occurrence of genes typically associated with the class 1 integrons in previously not studied environments with or without human impact and their association with IncP-1 plasmids. Total community DNA was extracted from manure-treated and untreated soils, lettuce and potato rhizosphere, digestates, and an on-farm biopurification system and screened by PCR with subsequent Southern blot hybridization for the presence of the class 1 integrase gene intI1 as well as qacE and qacEΔ1 resistance genes. The results revealed a widespread dissemination of class 1 integrons in the environments analyzed, mainly related to the presence of qacEΔ1 genes. All 28 IncP-1ε plasmids carrying class 1 integrons, which were captured exogenously in a recent study from piggery manure and soils treated with manure, carried qacEΔ1 genes. Based on the strong hybridization signals in the rhizosphere of lettuce compared to the potato rhizosphere, the abundances of intI1, qacE/qacEΔ1, and sul1 genes were quantified relative to the 16S rRNA gene abundance by real time PCR in the rhizosphere of lettuce planted in three different soils and in the corresponding bulk soil. A significant enrichment of intI1 and qacE/qacEΔ1 genes was confirmed in the rhizosphere of lettuce compared to bulk soil. Additionally, the relative abundance of korB genes specific for IncP-1 plasmids was enriched in the rhizosphere and correlated to the intI1 gene abundance indicating that IncP-1 plasmids might have contributed to the spread of class 1 integrons in the analyzed soils.